(untitled) (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2025)
This study aims to examine the influence of import duty and VAT rates on the import of K-POP albums and merchandise among GO TAEMINSTORE consumers. Using a quantitative approach and multiple linear regression analysis, this study analyzes data from 56 respondents who are active customers of GO TAEMINSTORE. The results of the analysis show a positive and significant simultaneous influence between the variables of import duty and VAT rates on the import of K-POP albums and merchandise. However, partially only the VAT variable has a significant effect on the import of K-POP albums and merchandise. This indicates that changes in VAT rates have a direct and real impact on consumers’ decisions to import these products. The contribution of both independent variables to the total coefficient of determination of the variation in import volume is 15.5%. These findings conclude that tax policies, especially VAT, play an important role in the dynamics of the K-POP album and merchandise import market. An increase in VAT rates tends to reduce imports, while a decrease in rates can encourage increased demand. The implications of this study for GO TAEMINSTORE are the need for a more adaptive strategy to changes in tax policies. In addition, providing transparent and accurate information about the applicable tax structure for imported products can help consumers in making purchasing decisions